A Model Explaining Social and Political Change of Party-states Structural and Dynamic Background of Similarities and Differences in Reproduction, reforms, Collapse and Transformation - Maria Csanadi (Hungarian Academy of Sciences, Institute of Economics, 2001)
I shall argue that the Interactive Party-State (IPS) model (Csanádi, 1997) allows us to place the Chinese and Hungarian party-state structure and dynamics into a common framework. This framework sheds light on the structural reasons behind the different functional effects of reforms. This paper is divided into three major parts. In the first section I summarize the structural and dynamic properties of the IPS model. This is followed by arguments raised regarding its general nature, and consequently, the applicability of the model to China based on common structural and operational grounds. Finally, I will reveal that behind the robust common ground, the different structural specifics may give rise to the divergent development paths. The primary focus is theoretical, with empirical examples provided. Consistent empirical analysis based on the model will be a following undertaking.
Keywords: 330